LOADS AND EFFECTS AFFECTING HYDROTECHNICAL CONSTRUCTION (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
This article provides information on the technical indicators of the 4K channel, which is located in the guard farm District of the Bukhara region. A study of the technical condition of the channel revealed deficiencies and provided a summary and suggestions for eliminating existing deficiencies and improving the technical condition.